2009
DOI: 10.7202/029567ar
|View full text |Cite
|
Sign up to set email alerts
|

La mobilité de la charge de fond des rivières torrentielles méditerranéennes

Abstract: La mobilité de la charge de fond de trois affluents de la Drôme (Barnavette, Béoux et Esconavette) a fait l’objet d’un suivi événementiel entre 1997 et 2002, au moyen d’un dispositif de terrain relativement simple permettant de mesurer les phénomènes de creusement et de remblaiement du lit, ainsi que la mise en mouvement des particules. Trois stations de mesure comprenant un ou plusieurs profils en travers pour le suivi topographique, un ensemble de chaînes d’érosion, des traceurs colorimétriques et un équipem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…For the purposes of this study, we shall only consider Note: When the value for Q b was not observed in the field, it was calculated using the formula proposed by Petit and Pauquet (1997): the scour chains installed on the riffles because, on this kind of site, it is well-known that the lateral differentiation of the shear stress is low (Petit, 1987). At each profile studied, five to six scour chains were placed transversally (Liébault and Clément, 2007). Given that there may be some small variations in the depth of the active layer at the same site, the average of the non-zero values observed at each site was used.…”
Section: Methodsmentioning
confidence: 99%
“…For the purposes of this study, we shall only consider Note: When the value for Q b was not observed in the field, it was calculated using the formula proposed by Petit and Pauquet (1997): the scour chains installed on the riffles because, on this kind of site, it is well-known that the lateral differentiation of the shear stress is low (Petit, 1987). At each profile studied, five to six scour chains were placed transversally (Liébault and Clément, 2007). Given that there may be some small variations in the depth of the active layer at the same site, the average of the non-zero values observed at each site was used.…”
Section: Methodsmentioning
confidence: 99%
“…The digging and filling of the bed were determined by erosion chains inserted vertically on the monitoring site [1]. At the same time, the distance traveled by the sediments was evaluated by the colorimetric particle tracing technique [6].…”
Section: Monitoring Of Sediment Mobilization Of the Bottom Of The Bedmentioning
confidence: 99%
“…Sediment transport is in many cases a fundamental issue in river management, such as flood protection works, bank erosion protection works, bridge and culvert construction, and construction of water reservoirs, dams, and any other hydraulic structures [3]. Many studies on solid transport have focused mainly on the quantification of the mobilized solid load, on the influence of hydraulic parameters, or on the study of transport at the particle scale [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Une lave torrentielle peut être définie comme un mouvement de terrain rapide, constitué d'un mélange d'eau, de débris organiques et de sédiments de toutes tailles, qui se produit généralement sous forme de bouffées, avec une concentration solide supérieure à 50 % (Coussot et Meunier, 1997 ;Chambon et Laigle, 2013 ;Liébault et al, 2013). Elles peuvent être de type granulaire ou cohésif en fonction de la granulométrie de la phase solide (Bonnet-Staub, 1998 ;Remaître et al, 2005).…”
unclassified